". . . In the Beginning I Was Frightened, Because Jews and Arabs Were Living Together . . . but Now I Don't Feel That There Are Jews and Arabs . . .": Palestinian Families in Israel Migrating in Search of Work. (September 2017) - Meler, Tal
Internal migration tendencies among Palestinian in Israel are limited by both internal and external barriers. Recently, however, it appears that many Palestinian families have migrated from the north of Israel southward to Beersheba in search of work. This article is based on qualitative research I conducted among Palestinian women in Israel who moved south because of economic and occupational hardship. These women find themselves tending to their households while living far from their families of origin and those of their husbands, confronting and adjusting to their new environment and coping with life in a "city of difference" in Jewish space and among the Arab-Bedouin population at work. Internal migration affects many areas of life, extending beyond the personal and family sphere to challenge the politics of expanse in Israel, which is grounded in segregative and exclusionary principles and blurs accepted lines in the Israeli educational system. This situation generates space for new dialogue, or alternatively delineates lines of separation and structures new urban and cultural segmentation processes. The article sheds light on the complexity of the nationalist-ethnic triangle that takes shape in cities and clarifies the women's experiences as they cross spatial and national borders—an unusual experience in Israeli life.